Maskot ‘Si Nara Singa’ sebagai Media Komunikasi Publik dan Strategi Dakwah Kultural KPU Kabupaten Kediri dalam Perspektif Studi Media Islam - Febry Nur Aisyiyah; Ellyda Retpitasari; Franisita Meisya Wardani; S. Antika Putri Hapsari; Silma Afifah (UIN Sunan Ampel Surabaya, 2025)
This study explores the role of the 2024 Kediri Regency General Election Commission (KPU) regional election mascot, Si Nara Singa, as a medium of public communication. Employing a qualitative research approach, data were collected through documentation, observation, and interviews. To analyze the symbolic and communicative aspects of the mascot’s design, the study applies Stuart Hall’s theory of representation. The findings offer a deeper understanding of how the mascot functions as an effective tool in disseminating information and engaging the public. The research draws upon two main data sources: primary data obtained from interviews, and secondary data from relevant literature and official documents. The KPU of Kediri Regency recognizes the strategic importance of public communication, particularly in the context of the 2024 general and local elections. Through initiatives such as traditional cultural art performances and the mascot parade (Kirab Maskot), the KPU leverages Si Nara Singa across multiple communication platforms to enhance transparency and boost voter participation. Overall, the mascot serves not only to represent the institution’s identity but also to foster emotional connection and active civic engagement within the local community.